Recent Advances in Upconversion Nanoparticles‐Based Multifunctional Nanocomposites for Combined Cancer Therapy. (27th October 2015) - Tian, Gan; Zhang, Xiao; Gu, Zhanjun; Zhao, Yuliang
Abstract : Lanthanide‐doped upconversion nanoparticles (UCNPs) have the ability to generate ultraviolet or visible emissions under continuous‐wave near‐infrared (NIR) excitation. Utilizing this special luminescence property, UCNPs are approved as a new generation of contrast agents in optical imaging with deep tissue‐penetration ability and high signal‐to‐noise ratio. The integration of UCNPs with other functional moieties can endow them with highly enriched functionalities for imaging‐guided cancer therapy, which makes composites based on UCNPs emerge as a new class of theranostic agents in biomedicine. Here, recent progress in combined cancer therapy using functional nanocomposites based on UCNPs is reviewed. Combined therapy referring to the co‐delivery of two or more therapeutic agents or a combination of different treatments is becoming more popular in clinical treatment of cancer because it generates synergistic anti‐cancer effects, reduces individual drug‐related toxicity and suppresses multi‐drug resistance through different mechanisms of action. Here, the recent advances of combined therapy contributed by UCNPs‐based nanocomposites on two main branches are reviewed: i) photodynamic therapy and ii) chemotherapy, which are the two most widely adopted therapies of UCNPs‐based composites. The future prospects and challenges in this emerging field will be also discussed. Abstract : Combined therapy, referring to the co‐delivery of two or more drugs or a combination of different treatments, is becoming popular in clinical cancer therapy due to its synergistic anti‐cancer effect, reduced drug‐related toxicity, and multi‐drug resistance reversal capability. Recent progress in combined cancer therapy using functional nanocomposites based on upconversion nanoparticles (UCNPs) is reviewed.